2006
DOI: 10.1177/107110070602700301
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Lesions of the Talus: Change in MRI Findings Over Time in Talar Lesions Without Operative Intervention and Implications for Staging Systems

Abstract: OLT did not invariably progress over the short-term without operative intervention. Because some cysts and bone marrow edema resolved on MRI, they may not be reliable signs of lesion severity nor show progression of degenerative changes. Since these findings determine the stage and severity of OLT in some staging systems, they may require reconsideration and adjustment of the current staging systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 22 publications
(62 reference statements)
2
51
1
2
Order By: Relevance
“…This rate of ankle osteoarthritis in patients with OLT is comparable with data from earlier studies. 4,7,12,18,21 Bauer et al 2 described the development of severe ankle osteoarthritis after an average follow-up of 21 years in only 1 of 30 patients having OLT. In our study population, only 1 patient demonstrated a stage progression from 0 to 1 on the van Dijk classification, 22 whereas all others remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate of ankle osteoarthritis in patients with OLT is comparable with data from earlier studies. 4,7,12,18,21 Bauer et al 2 described the development of severe ankle osteoarthritis after an average follow-up of 21 years in only 1 of 30 patients having OLT. In our study population, only 1 patient demonstrated a stage progression from 0 to 1 on the van Dijk classification, 22 whereas all others remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,12,15,18 The natural history of OLTs is not well described. It is unclear whether these lesions tend to progress in terms of size and symptoms or lead to joint deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Histological examination revealed two distinct patterns in the samples: (1) thick homogeneous hyaline cartilage alone with little Wbrous tissue surrounding areas of separation and (2) nearly normal, thin hyaline cartilage above a mixed layer of hyaline cartilage and subchondral trabeculae and Wbrous/Wbro-cartilaginous tissue at the areas of separation, indicating delayed or non-union. BML is present in 50% of cases [34], but the relation between emergence of BML and progression in this disease is still subject to debate [35].…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…Other signs of an unstable OCL are focal cartilage defects or defects in the subchondral bony end plate, the presence of subchondral cysts or an empty bony defect zone filled with fluid [25,29]. However, mechanical stability assessment alone, based on MRI findings, has also been critically discussed [41], and one study of the knee demonstrated no relationship between the size and localization of an OCL and its stability [42]. The aforementioned signs of instability of an OCL apply to adults and adolescents with closed epiphyseal plates [25,43].…”
Section: Classification Of Osteochondral Lesionsmentioning
confidence: 99%